Endocytosis of Activated Muscarinic m2 Receptor (m2R) in Live Mouse Hippocampal Neurons Occurs via a Clathrin-Dependent Pathway - Lambert, Lisa; Dubayle, David; Fafouri, Assia; Herzog, Etienne; Csaba, Zsolt; Dournaud, Pascal; El Mestikawy, Salah; Bernard, Véronique (Frontiers in Cellular Neuroscience, 2018)
Our aim was to examine the dynamics of the muscarinic m2 receptor (m2R), a G-protein coupled receptor (GPCR), after agonist activation in living hippocampal neurons, and especially clathrin dependency endocytosis. We have previously shown that the m2R undergoes agonist-induced internalization in vivo. However, the nature of the endocytotic pathway used by m2R after activation is still unknown in living neurons. Using live cell imaging and quantitative analyses, we have monitored the effect of stimulation on the fate of the membrane-bound m2R and on its redistribution in intraneuronal compartments. Shortly (6 min) after activation, m2R is internalized into clathrin immunopositive structures. Furthermore, after clathrin-dependent endocytosis, m2R associates with early and late endosomes and with subcellular organelles involved in degradation. Together, these results provide, for the first time, a description of m2R trafficking in living neurons and prove that m2R undergoes clathrin-dependent endocytosis before being degraded.